HAJI UMA DALAM PARADIGMA DEKONSTRUKSI PEMBERITAAN MEDIA - Gadeng, Irwan (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This study aims to analyze and deconstruct the political-social image of Haji Uma, a Regional Representative Council (DPD RI) senator from Aceh, known for his social activities and background as a local comedy film actor. The research focuses on how the media constructs Haji Uma's image of compassion and the extent to which this image functions as a political branding strategy rather than substantive advocacy for Acehnese aspirations at the national level. Employing Derrida's deconstruction approach, the study dissects dominant narratives shaped by media coverage, comparing them with public perception and institutional performance realities. Data were collected through in-depth interviews with academics, along with literature review and media content analysis. The findings reveal that Haji Uma's social activity strategies hold strong empathetic value in the public eye but are also systematically utilized as political image-building tools to enhance popularity without demonstrating deep engagement in substantive policy advocacy. This study uncovers an imbalance between symbolic representation in the public sphere and strategic responsibility as a DPD RI member